Advances in mode of action of antimalarials and resistance mechanisms 2 - Warhurst, David (Henry Stewart Talks, 2013)
Drug resistance mechanisms, Chloroquine-resistance in falciparum malaria, PfCRT protein -Resistance to artemisinin, PgH-1, Rationale for Artemisinin combination therapy, Controlling the spread of resistance, Approach to urgent treatment for severe malaria, Intermittent preventive treatment